(untitled) (Research, Society and Development, 2020)
The extension is an essential academic practice in universities, associated with teaching and research. In initial or continuing teacher education courses the extension actions may promote the integration of theory and practice, approaching the University to the Basic Education. In this article we present and discuss the dynamics of developing an extension course, aimed to mathematics teachers training, held at the Federal University of ABC (UFABC) in the city of Santo André, SP. The course aimed to provide participants with involvement with interdisciplinary themes through the integration between Project Work and Mathematical Modelling. Our aim in this article is to analyze the course’s contributions to both education and practice of the teachers. As data we have used records and productions of participants, including their statements. Through the qualitative methodology, we analyzed the data trying to identify, in the participants’ manifestations, indications of possible contributions of the activities developed for the initial, continued formation and for the teaching practice We have identified that the course provided teachers in training with a new perspective of the Mathematics and Education, encouraging alternative practices to the so-called traditional classes, such as Thematic Projects and Mathematical Modelling, which proved to be viable for the school at different levels, from the experience of this type of practice in the course.